KARAKTERISASI SILIKA DARI ABU AMPAS TEBU - Tifa Paramitha; Tri Reksa Saputra; Amelia Nur Aliah; Arijan Vevayose Tarigan; Mukhtar Ghozali (KOVALEN: Jurnal Riset Kimia, 2019)
Silica has been successfully extracted from sugarcane bagasse ash by using alkali method. Extraction was carried out using sodium hydroxide solution to obtain sodium silicate solution and solid residue. Then, hydrochloric acid solution was added to sodium silicate solution until pH of solution was 7 and silica was formed. Furthermore, silica was heated in oven at 150 ˚C and calcined at 700 ˚C. Variation of this study were extraction time (1, 2 and 3 hours). The synthesized silica were characterized functional groups, acidity level, water adsorption ability and adsorption ability of Cu2+ ion. The results of FTIR analysis showed that all silica contain siloxane group. Silanol group did not appear because during calcination process occured the condensation reaction of silanol group. Other characterization results showed that silica with extraction time of 2 hours had highest acidity level, water adsorption ability and adsorption ability of Cu2+ ion, which were 6.201 mmol/gram, 86.41% and 92.55%. Keywords : bagasse ash, extraction, silica, siloxane